2018
DOI: 10.1029/2018gl078837
|View full text |Cite
|
Sign up to set email alerts
|

Similarity in Fog and Rainfall Intermittency

Abstract: Intermittent fog occurrences supply significant amounts of moisture to plants in the form of fog drip onto the soil surface thereby prompting interest in their statistical behavior at multiple timescales. A comparison of rainfall and fog measurements collected at an inland tropical cloud forest in Kenya and a coastal rangeland in Northern California is presented to explore whether fog occurrences have similar intermittency characteristics as rainfall. The results confirm that both rainfall and fog show approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…Our LST estimation using the satellite image was only a snapshot for July 4, 2019, from a sunny almost cloud-free day, and does not represent the year-round situation experiencing two rainy seasons, which are cloudy. In the hills, cloudy and misty conditions are experienced throughout the year (Helle, 2016;Räsänen et al, 2018). A time series comparing the cooling effect of CC over seasons and several years is an interesting future research topic, as the TOMST sensors remained in the 19 field plots.…”
Section: Discussionmentioning
confidence: 99%
“…Our LST estimation using the satellite image was only a snapshot for July 4, 2019, from a sunny almost cloud-free day, and does not represent the year-round situation experiencing two rainy seasons, which are cloudy. In the hills, cloudy and misty conditions are experienced throughout the year (Helle, 2016;Räsänen et al, 2018). A time series comparing the cooling effect of CC over seasons and several years is an interesting future research topic, as the TOMST sensors remained in the 19 field plots.…”
Section: Discussionmentioning
confidence: 99%
“…As previously discussed, in [100] a DFA analysis for rainfall was carried out, which showed that this two-range pattern for rainfall series is associated with the binary structure of the time series (the pattern of alternating dry and wet spells independently of the actual values of rainfall intensity. Recently, in [401] it has been shown that rainfall and fog events have a similar structure in terms of on-off intermittency properties. This two ranges pattern with characteristic time has been also shown in other persistence-based studies dealing with DFA such as, orographic fog events [162], SSTA data [132], rainfall time series [22], soil moisture [146] or water level in reservoirs [167], among others.…”
Section: Dfa and Characteristic Timementioning
confidence: 99%
“…Generally, most of the total precipitation recorded at a station is delivered over only a few days with heavy rain, while the many days with light drizzle contribute much less to the total (Pendergrass and Knutti, 2018; Rasanen et al ., 2018). The asymmetric nature of precipitation temporal distribution has been widely examined by many researchers, which is aggravated due to climate change (Chang et al ., 2016; Zhou and Wang, 2017; Cindric et al ., 2019; Li et al ., 2020b).…”
Section: Introductionmentioning
confidence: 99%